1998
DOI: 10.1023/a:1022146130836
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Calls to Israeli Hotlines During the Gulf War

Abstract: The current study presents results of a survey of 3,215 calls received at seven centers of telephone emergency services (TES) in Israel during the Gulf War, when citizens of Israel experienced severe stress resulting from SCUD missile attacks. Whereas former surveys have shown that characteristics of calls to TES in Israel are generally not affected by external stressogenic events, a remarkable change was recorded in both the quantity and quality of calls received in TES centers in Israel during the Gulf War. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…The list of problems was derived on the basis of content analysis of calls to ERAN that yielded six major categories. This instrument was used to operationalize the caller's main problem in former studies (Gilat, Lobel & Gil, 1998;Latzer & Gilat, 2000).…”
Section: Mesures and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of problems was derived on the basis of content analysis of calls to ERAN that yielded six major categories. This instrument was used to operationalize the caller's main problem in former studies (Gilat, Lobel & Gil, 1998;Latzer & Gilat, 2000).…”
Section: Mesures and Variablesmentioning
confidence: 99%
“…Thus, hotlines may be perceived as an attractive source of help during community crises when physical danger is experienced, among individuals who had not used formal sources of psychological help before. Indeed, a study on the calls to ERAN during the 1991 Gulf War (Gilat, Lobel, & Gil, 1998) revealed a significant increase not only in the number of calls to the hotline but also in the proportion of new callers that had not sought psychological help before the war. Thus, we hypothesized that ERAN would serve as an important source of community help for Israelis experiencing stress due to the Intifada.…”
mentioning
confidence: 99%
“…326 I. Gilat and S. Rosenau The study was conducted within the context of the Israeli Association for Emotional First Aid (ERAN), a volunteer-based community mental health service that offers help by means of telephone helplines and the internet, and is well known to the Israeli public (Gilat, Lobel, & Gil, 1998). ERAN is guided by the principles of caller anonymity, volunteer anonymity, assistance with a variety of problems, and high availability.…”
mentioning
confidence: 99%
“…A crisis may be personal (i.e., pertaining to a stressful individual event) or environmental (i.e., affecting an entire community; Gilat, Lobel, & Gil, 1998). Therefore, social workers need to be prepared and understand the micro-and macro-perspectives of addressing natural disasters.…”
Section: Resultsmentioning
confidence: 99%